Drug Retention Rate and Predictive Factors of Drug Survival for Interleukin-1 Inhibitors in Systemic Juvenile Idiopathic Arthritis - Sota, Jurgen; Insalaco, Antonella; Cimaz, Rolando; Alessio, Maria; Cattalini, Marco; Gallizzi, Romina; Maggio, Maria Cristina; Lopalco, Giuseppe; La Torre, Francesco; Fabiani, Claudia; Pardeo, Manuela; Olivieri, Alma Nunzia; et al. (Frontiers in Pharmacology, 2019)
Background and Objectives: Few studies have reported the drug retention rate (DRR) of biologic drugs in juvenile idiopathic arthritis (JIA), and none of them has specifically investigated the DRR of interleukin (IL)-1 inhibitors on systemic JIA (sJIA). This study aims to describe IL-1 inhibitors DRR and evaluate predictive factors of drug survival based on data from a real-world setting concerning sJIA. Methods: Medical records from sJIA patients treated with anakinra (ANA) and canakinumab (CAN) were retrospectively analyzed from 15 Italian tertiary referral centers. Results: Seventy seven patients were enrolled for a total of 86 treatment courses. The cumulative retention rate of the IL-1 inhibitors at 12-, 24-, 48-, and 60-months of follow-up was 79.9, 59.5, 53.5, and 53.5%, respectively, without any statistically significant differences between ANA and CAN (p = 0.056), and between patients treated in monotherapy compared to the subgroup co-administered with conventional immunosuppressors (p = 0.058). On the contrary, significant differences were found between biologic-naive patients and those previously treated with biologic drugs (p = 0.038) and when distinguishing according to adverse events (AEs) occurrence (p = 0.04). In regression analysis, patients pre-treated with other biologics (HR = 3.357 [CI: 1.341–8.406], p = 0.01) and those experiencing AEs (HR = 2.970 [CI: 1.186–7.435], p = 0.020) were associated with a higher hazard ratio of IL-1 inhibitors withdrawal. The mean treatment delay was significantly higher among patients discontinuing IL-1 inhibitors (p = 0.0002). Conclusions: Our findings suggest an excellent overall DRR for both ANA and CAN that might be further augmented by paying attention to AEs and employing these agents as first-line biologics in an early disease phase.